Short-Term Results after Total Trapeziectomy with a Poly-L/D-Lactide Spacer - Van Royen, Kjell; Kestens, Bart; Van Laere, Sven; Goubau, Jean; Goorens, Chul Ki (Journal of Wrist Surgery, 2018)
Background Proximal migration of the first metacarpal can be seen after total trapeziectomy and various techniques have been described to prevent this subsidence.Purpose We hypothesized the insertion of a poly-L/D-lactide spacer to prevent proximal migration of the first metacarpal without the need of an additional ligament reconstruction, allowing early mobilization and less demanding rehabilitation.Patients and Methods Ten thumbs were treated with a total trapeziectomy and insertion of a poly-L/D-lactide scaffold. Clinical and radiological evaluation was performed after 6 months and 1 year. Patient satisfaction, pain, Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) score, mobility of the thumb, and strength were assessed.Results Pain according to the visual analog scale decreased (p = 0.01) and QuickDASH score decreased (p = 0.02) significantly after 1 year. Radiological evaluation after 12 months showed a collapse of the scaphometacarpal distance of 45% (p = 0.01). Osteolysis of the distal scaphoid pole and/or proximal metacarpal was seen in 6 out of 10 cases. Because of the osteolysis, the use of the poly-L/D-lactide scaffold was discontinued in our practice.Conclusion In this limited series, total trapeziectomy with the use of the poly-L/D-lactide scaffold provides significant pain reduction and improvement of overall function. Radiographic evaluation shows significant collapse of the scaphometacarpal distance after 1 year and frequent signs of osteolysis. We do not encourage the use of the poly-L/D-lactide scaffold with total trapeziectomy before long-term clinical and radiological follow-ups of the osteolysis are available.
Keywords: trapeziometacarpal osteoarthritis; poly-L/D-lactide spacer; osteolysis; proximal migration